Role of Free Will in Henrik Ibsen’s The Lady from the Sea: Exploring Women's Free Will in a Male-Dominated Society (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The aim of the present research paper is to highlight the role of free will in Norwegian playwright Henrik Ibsen’s play The Lady from the Sea. Henrik Ibsen endeavours to present the actual conditions of women in a male-dominated society. Apart from dealing with the various aspects including education, freedom, self-identity, he particularly deals with the theme of free will pertaining to women. The research paper exhibits how women’s free will is controlled and manipulated in a patriarchal society just to meet its own vested interests. Henrik Ibsen’s characters in this play are liberal in thinking as well in approach. Unlike his other plays, the present play breaks off all the restrictions created by men in a male-dominated society.